Analisis Strategi Pemasaran Oleh Sales Promotion Girl Event Pada Penjualan Produk Mie Sukses Isi 2 - Edgina Hartahartina; Salsabil Putri N; Shaldan Alqaisha; Risna Haryati (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to explain whether the marketing strategy of the Sales Promotion Girl (SPG) event influences the sales volume of successful 2-filled noodle products at PT. Wings Food Bandung. This research uses a qualitative research. Data collection was carried out by interviewing Sales Promotion Girls (SPG). The interview technique used was semi-structured (Semi Structured Qualitative Interview). Based on the research results, it can be concluded that SPG is at the forefront in communicating directly with the public to introduce and promote products. They are required to have an attractive appearance, a minimum height of 160 cm, marketing skills, product knowledge, and be able to work according to targets. They also use various promotional techniques, such as providing explanations about products, making sales, giving souvenirs, and holding raffles or door prizes. Apart from that, there are differences between regular SPGs and event SPGs, as well as recruitment criteria that must be met by an SPG, such as having an attractive appearance, a maximum age of 25 years, and having the ability to promote goods.